Challenges in green building development implemented in Johor Bahru, Johor / Karina Natasya Kamaruzaman - Kamaruzaman, Karina Natasya (2023)
Green building has been highlighted as the current trend in environmental conservation. Green practises and ideas in housing development have been proven to offer an obvious positive contribution to the environment. To implement and practise green in the construction projects, developers are being drawn to and restrained by a number of advantages and obstacles. Even though green building has been shown to have a substantial positive influence on the environment and has been used in Malaysia construction industry for around 10 years, few green concepts are seen in actual construction projects. Therefore, this study is conducted to identify the obstacles that restrict the implementation of green building in Johor Bahru, Johor. The pre-construction stage to the post-construction stage of the construction projects are all evaluated using a qualitative approach. 3 massive involved person in green building construction and developer in Johor Bahru construction industry have been selected to participate in this research study to gather their invaluable insight and opinions on the use of green practises on their current and previous construction projects.